David Wojnarowicz and the Surge of Nuances - Paul R Abramson; Tania Love Abramson (Aesthetic Investigations, 2019)
When looking at two paintings, ostensibly by Rembrandt, is there an aesthetic difference in how these paintings are perceived if we know that one of the two paintings is a forgery? Most certainly, declared Nelson Goodman (1976). Knowledge of the difference would modify the aesthetic experience. When looking at Michelangelo’s Christ on the Cross, the result is arguably similar. What we see depends on what we know about Christ’s story. The same might also be said more generally about tragic narratives and their accompanying indicia. Awareness impacts viewers acutely. This is especially evident in curated Holocaust memorials, where the ghastly artifacts, and the unfathomable story lines, are intrinsic to their aesthetic force. This insight however is by no means limited to curated monuments. Learning that an artist, David Wojnarowicz for example, was a victim of inconceivable torment is no less critical to how their artworks are perceived. Our argument, in its totality, is that being informed is preferable to unknowing, and that knowing, however manifested, has the capacity of modifying visual perception.